The Influence of Problem Solving Learning Model on Students' Mathematic Problem Solving Ability in SMA Private High School, Nommensen Pematangsiantar Campus - Sitompul, Betty Magdalena; Sidabutar, Ropinus; Purba, Yoel Octobe (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study was to determine the effect of the Problem-Solving learning model on the Mathematical Problem-Solving Ability of Class XI Students of Private High School Nommensen Pematangsiantar Campus. The design of this study used a pretest-posttest control group design. The population and sample in this study were all students of class XI Private High School Nommensen Pematangsiantar T.A 2022/2023 Campus, totaling 62 students. The instruments used in this study are validity, reliability, level of difficulty of test items and distinguishing power of test items. The data obtained were then analyzed using data analysis techniques, the average value of the results of the Problem-Solving learning model on students' mathematical problem abilities was 63.39. The results of hypothesis testing after obtained zcount = 2.530 and ztable = 1.960 This means that tcount is greater than ttable which indicates the hypothesis H0 is rejected. Based on the description, it is concluded that the use of the Problem-Solving learning model has an influence on students' mathematical problem-solving abilities in learning the Composition Functions of the Private High School, Pematangsiantar Campus